Determination of optimum heap height from column leach tests: 1. Model development and initial results. (3rd July 2017) - Apelt, T.; Forrester, K.; Short, M.; Stefan, L.
Abstract : A method to determine optimum heap leach height has resulted from design work for a uranium heap leach project on the Macusani Plateau in south-eastern Peru. The on-off/racetrack heap leach process, the base case design parameters and the relevant column leach test results are described. In the problem development, a maximum leach extraction versus grade relationship, the leach extraction model, a recovery discount model, the financial parameters utilised and the calculation sequence are described before a spreadsheet solution for optimum heap height is presented. Equations used in the spreadsheet solution are detailed in the algebraic optimisation problem formulation. Symbolic solution proved too challenging for the computer algebra system utilised (Maxima). The subsequent algebraic simplification to the leach extraction model yields a succinct solution for an optimum heap height estimate. The estimate is affected by recovery discount and pad maintenance costs but is independent of theoretical recovery and pad capital costs. The initial results were approximately 50% of the spreadsheet calculation results. A correction factor is required to compensate.